A Recontextualização do Currículo Integrado do Curso de Enfermagem da Universidade Federal de São João del Rei, Minas Gerais - Elaine Cristina Dias Franco (2016)
Case study using qualitative approach, analytical theoretical framework based on Ball & Bowee Policy Cycle and Bernsteins Recontextualization Theory. The goal of the study is to analyze the recontextualization process of the integrated course curriculum adopted by the undergraduate nursing degree course at the Federal University of São João del-Rei, Minas Gerais. Curriculum is approached in this study as a political and cultural artifact, marked by recontextualization processes occurring across and in the Contexts of Influence, Policy Text Production and Practice that compose Policy Cycle. Social actors participating in the study are Nursing course teachers. The data were collected, between the months of May and September 2014, by means of (1) systematic observation of teaching practice, (2) conduction of interviews with the teachers observed and teachers involved in curriculum development, and (3) documentary analysis of Pedagogical Project. Empricial data were analyzed using Faircloughs Critical Discourse Analysis. Findings indicate that in the Contexts of Influence and Policy Text Production, the curriculum is the result of a bricolage of educational policies, health policies, and experiences of other institutions. In the Practice Context, observing from the teachers understanding of the integrated curriculum, their class planning and teaching practices, teachers have been seen to endeavor to adopt, to a certain extent, the teaching practices of the integrated curriculum when they plan and conduct their classes based on notions of the practice of dialogics and problem-presenting. However, when teachers associate information transmission to these notions, elements from traditional curriculum are noticeably present as benchmarks, constituting thus a limiting factor for realization of the integrated curriculum. On analysis of the recontextualization process of the integrated curriculum across and in Policy Cycle contexts, it was seen that organization-related weaknesses in modular structure and scant teacher participation in Policy Text Production Context, allied with education and previous traditional teaching experience, favor recontextualization of curricular proposal, when translated into the Context of Practice. Thus, we conclude that teacher instruction and continued teacher training are necessary to ensure teachers adopt the teaching practices from the integrated curriculum perspective, by means of systematic and participatory curriculum assessment. Such participatory assessment results in the exercise of new modes of teacher subjectivation with implications for the production of curricular innovations.